The Cascade Effect of Parent Dysfunction: An Emotion Socialization Transmission Framework - Seddon, Jessica A.; Abdel-Baki, Rita; Feige, Sarah; Thomassin, Kristel (Frontiers in Psychology, 2020)
The current study tested a preliminary cascade model of parent dysfunction—i.e., internalizing psychopathology and emotion dysregulation—whereby parent dysfunction is transmitted to children through the impact of parental emotion socialization on child emotion regulation. Participants were 705 mothers (Mage = 36.17, SD = 7.55) and fathers (Mage = 35.43, SD = 6.49) of children aged 8 to 12 years who self-reported on their internalizing psychopathology, emotion regulation difficulties, and emotion socialization practices, and on their child’s internalizing psychopathology and emotion regulation. Using a split sample method, we employed a data-driven approach to develop a conceptual model from our initially proposed theoretical model with the first subsample (n = 352, 51% mothers), and then validated this model in a second subsample (n = 353, 49% mothers). Results supported a model in which the transmission of dysfunction from parent to child was sequentially mediated by unsupportive parental emotion socialization—but not supportive parental emotion socialization—and child emotion dysregulation. The indirect effects from the final model did not differ by parent gender. Findings provide preliminary support for a mechanism by which maternal and paternal internalizing psychopathology and emotion dysregulation disrupt parental emotion socialization by increasing unsupportive emotion socialization practices, which impacts children’s development of emotion regulation skills and risk for internalizing psychopathology.